Diferenças entre as percepções de mães encarceradas e mães externas ao cárcere quanto ao exercício da maternidade - Cabianca, Letícia Moraes (Universidade Federal de São Carlos, 2023)
The various considerations regarding the exercise of motherhood made “being a mother” a central issue in several studies, which reiterate the different facets of motherhood depending on the context in which it is seen. One of the contexts in which motherhood expresses delicate consequences is the Brazilian prison environment, a scenario of immeasurable vulnerability. In this sense, there are studies on the meanings of motherhood for incarcerated mothers, in addition to countless studies on these meanings for mothers who are located outside the prison environment. However, no studies were found with comparative analysis between the two groups of meanings. Given the lack of comparative studies, added to the increasing number of women who share the prison environment with their children, this study aims to analyze the perceptions of incarcerated mothers and the perceptions of mothers who are located outside the prison environment regarding the exercise of motherhood, seeking to identify similarities and differences in the mothering process. To this end, 10 mothers whose children were up to 6 months old participated in the study, 5 of them incarcerated and the other 5 outside prison. These mothers were recruited so that the participants were equivalent to each other in terms of sociodemographic variables (age, income, education, self-declaration of color and marital status) and number of children, in order to minimize the effects of these variables on the results found. The participants answered a questionnaire characterizing the participants, the Critério Brasil for categorization into a socioeconomic class, a scale for analyzing their social support (EPSUS-A) and a semi-structured interview to obtain their perceptions about the exercise of motherhood. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. As a result, similarities were identified between the two groups of mothers in terms of perceived social support, feelings of discovering the pregnancy and the existence of suffering and concerns in motherhood; while differences were identified related to discomfort regarding the body changes triggered by pregnancy, the type of aspect most highlighted in childbirth, the presence of obstetric violence, issues involved in breastfeeding, the degree of support for motherhood performance, the perception of themselves as mothers and the type of suffering most faced. It was concluded that the context where motherhood is exercised has an influence on perceptions regarding its exercise.
Differences between the perceptions of more incarcerated and more out-of-prisoners about motherhood
Keywords: Cárcere; Maternidade; Mães; Percepções; Prisão; Significados; Prison; Motherhood; Mother; Perceptions; Meanings; CIENCIAS HUMANAS::PSICOLOGIA